Influence of methoxy-substituents on the strength of Br ... Br type II halogen bonds in bromobenzoic acid - Raffo, Pablo Alejandro (2016)
4-bromo-3,5-di(methoxy)benzoic acid (I) crystallizes in the monoclinic C2/c space group, a = 22.3405 (6) Å, b = 4.85142 (14) Å, c = 18.1583 (5) Å, β = 93.086 (2)°. The crystal structure shows head-to-head dimeric units linked via type II Br ... Br interactions as well as Br ... π and weak H-bonding interactions. The whole structure exhibits features similar to those of the parent 4-bromobenzoic acid (II), most notably the overall geometrical features involved in the Br ... Br type II interactions. Both structures display comparable C-Br ... Br angles (θ1 = 98.3 and 91.6° and θ2 = 163.0 and 163.5° for (I) and (II) respectively), but the Br ... Br distance is significantly shorter in (I) (3.58 Å) than in (II) (3.81 Å). QM computations provide the magnitude of the intermolecular interactions present in both (I) and (II), and allow disclosing the individual covalent and electrostatic contributions to the Br-Br halogen bond in terms of interaction energies, electrostatic potentials, and a molecular orbital (MO) analysis.